Successful treatment of paraneoplastic hypercalcemia in a patient with giant condyloma acuminatum: a case report - Linnemann, Thomas (BioMed Central, 2013)
INTRODUCTION: While paraneoplastic syndromes in patients with malignant and metastasizing tumors are common, they are rarely associated with skin tumors showing predominantly local growth patterns. This case report relates to a patient with giant condyloma acuminatum, also called Buschke-Löwenstein tumor, with paraneoplastic hypercalcemia, who was successfully treated with conservative treatment. CASE PRESENTATION: The patient in question is a 48-year-old German man with a giant periscrotal tumor. Before and during the therapy, two episodes of symptomatic hypercalcemia occurred, which were successfully treated by bisphosphonates, intravenous fluids and diuretics. No evidence of lytic bone affection was found. CONCLUSIONS: Paraneoplastic hypercalcemia may occur in patients who have a Buschke-Löwenstein tumor. For patients, where surgery is not an option, established medical therapies like bisphosphonates may be useful in addition to diuretics and infusions.